PENGARUH OVERALL CONVENIENCE ONLINE SHOPPING SHOPEE TERHADAP BEHAVIORAL INTETION DI SURABAYA - Shella Dwi Cahyanti; Siti Rahayu; Erna Andajani (CALYPTRA, 2018)
The purpose of this research is to know the perception and behavior of online Shoppers purchasing after shopping using application at Shopee and to know the overall relationship of Shopee's convenience to behavior intention in Surabaya. The sample used is people who have done online shopping in Shopee. The method used in this research is second order.This research uses the help of SPPS 18 for windows and AMOS 20 program. From the research conducted, it is found that overall convenience affect the behavioral intention on Shopee online website in Surabaya.